CircPRKCI relieves lipopolysaccharide‐induced HK2 cell injury by upregulating the expression of miR‐545 target gene ZEB2. (27th February 2020) - Shi, Xiaofeng; Ma, Wei; Li, Yongqi; Wang, Han; Pan, Shuang; Pan, Yongquan; Xu, Caiming; Li, Lei
Abstract: The aim of this study was to investigate the possible influences of circPRKCI abnormal expression on lipopolysaccharide (LPS)‐induced HK2 cell injury and its mechanism. The circPRKCI level was identified in serum samples from patients with urosepsis and healthy subjects, as well as LPS‐treated HK2 cells by qRT‐PCR. Cell viability, apoptosis, expression of proteins associated with apoptosis, and expression of pro‐inflammatory cytokines in LPS‐treated HK2 cells were measured. Effects of circPRKCI abnormal expression on LPS‐induced HK2 cell injury were then evaluated. Afterward, the binding miRNA of circPRKCI and target gene of miRNA were identified, and the involvements of NF‐kB pathway signaling pathway with the effects of circPRKCI were finally studied. CircPRKCI was significantly down‐regulated in serum samples from patients with urosepsis and LPS‐treated HK2 cells. LPS‐induced decrease of cell viability, increase of cell apoptosis, as well as elevated productions of tumor necrosis factor (TNF)‐α, interleukins (IL)‐1β, IL‐6, and IL‐8 in HK2 cells were attenuated by overexpressed circPRKCI. In addition, circPRKCI negatively regulated the expression of miR‐545, and miR‐545 up‐regulation reversed the inhibiting effects of circPRKCI overexpression on LPS‐induced HK2 cell injury. Moreover, zinc finger E‐box‐binding homeobox 2 (ZEB2) was identified as a target gene of miR‐545, and ZEB2 overexpression partly reversed the effects of miR‐545 up‐regulation on LPS‐induced HK2 cell injury. Furthermore, NF‐kB pathway was revealed to be associated to the effects of circPRKCI on LPS‐induced HK2 cell injury. This research indicated that the highly expressed circPRKCI relieved inflammatory injury induced by LPS in HK2 cells by suppressing miR‐545/ZEBs and depressing the briskness of NF‐kB pathway.